Identification of the active site of human mitochondrial malonyl‐coenzyme a decarboxylase: A combined computational study. Issue 6 (25th March 2016) - Ling, Baoping; Liu, Yuxia; Li, Xiaoping; Wang, Zhiguo; Bi, Siwei
ABSTRACT: Malonyl‐CoA decarboxylase (MCD) can control the level of malonyl‐CoA in cell through the decarboxylation of malonyl‐CoA to acetyl‐CoA, and plays an essential role in regulating fatty acid metabolism, thus it is a potential target for drug discovery. However, the interactions of MCD with CoA derivatives are not well understood owing to unavailable crystal structure with a complete occupancy in the active site. To identify the active site of MCD, molecular docking and molecular dynamics simulations were performed to explore the interactions of human mitochondrial MCD (HmMCD) and CoA derivatives. The findings reveal that the active site of HmMCD indeed resides in the prominent groove which resembles that of CurA. However, the binding modes are slightly different from the one observed in CurA due to the occupancy of the side chain of Lys183 from the N‐terminal helical domain instead of the adenine ring of CoA. The residues 300 − 305 play an essential role in maintaining the stability of complex mainly through hydrogen bond interactions with the pyrophosphate moiety of acetyl‐CoA. Principle component analysis elucidates the conformational distribution and dominant concerted motions of HmMCD. MM_PBSA calculations present the crucial residues and the major driving force responsible for the binding of acetyl‐CoA. These results provide useful information for understanding the interactions of HmMCD with CoA derivatives. Proteins 2016; 84:792–802. © 2016 Wiley Periodicals, Inc.